Additive transcriptomic variation associated with reproductive traits suggest local adaptation in a recently settled population of the Pacific oyster, Crassostrea gigas. (December 2015) - Sussarellu, Rossana; Huvet, Arnaud; Lapègue, Sylvie; Quillen, Virgile; Lelong, Christophe; Cornette, Florence; Jensen, Lasse; Bierne, Nicolas; Boudry, Pierre
Abstract Background Originating from Northeast Asia, the Pacific oysterCrassostrea gigas has been introduced into a large number of countries for aquaculture purpose. Following introduction, the Pacific oyster has turned into an invasive species in an increasing number of coastal areas, notably recently in Northern Europe. Methods To explore potential adaptation of reproductive traits in populations with different histories, we set up a common garden experiment based on the comparison of progenies from two populations of Pacific oyster sampled in France and Denmark and their hybrids. Sex ratio, condition index and microarray gene expression in gonads, were analyzed in each progeny (n  = 60). Results A female-biased sex-ratio and a higher condition index were observed in the Danish progeny, possibly reflecting an evolutionary reproductive strategy to increase the potential success of natural recruitment in recently settled population. Using multifarious statistical approaches and accounting for sex differences we identified several transcripts differentially expressed between the Danish and French progenies, for which additive genetic basis is suspected (showing intermediate expression levels in hybrids, and therefore additivity). Candidate transcripts included mRNA coding for sperm quality and insulin metabolism, known to be implicated in coordinated control and success of reproduction. Conclusions Observed differences suggest that adaptation of invasive populations might have occurred during expansion acting on reproductive traits, and in particular on a female-biased sex-ratio, gamete quality and fertility.